DESIGN OPTIMIZATION OF BODY ARMOR STRUCTURE WITH HYBRID METAL - CELLULOSE NANOCRYSTALLINE COMPOSITE UNDERGOING BALLISTIC IMPACT - Ilha, Fatih
The development of high-velocity projectiles and explosives has encouraged the development of body armor to be reliable, more flexible, lighter, and high energy-absorbing capabilities. One of the inovation to the development of body armor is using composite from Nanocrystalline Cellulose fiber which has high strength-to-weight ratio and can be integrated into composites to provide thus providing optimal balance between protection, lightness, and flexibility. The structure based on hybrid metal - composite are potentially stronger than the existing body armor. This research employs numerical simulation using the finite element method for ballistic impact on body armor structures, utilizing the LS-DYNA application. The body armor structure is composed of a composite material with Nanocrystalline Cellulose fibers hybridized with metal. The study also involves variations in metal thickness, composite thickness, and composite orientation. Optimization is conducted to achieve the defined resistance according to the NIJ 0101.06 standard for Body Armor Level III against 7.62 mm Full Metal Jacket (FMJ) bullets with a velocity of 847 m/s at a distance of 15 m. The optimization method used is Design for Six-Sigma (DFSS) with the Taguchi method and ANOVA, combining specified parameters to obtain an optimum structural configuration for specific energy absorption (SEA) and cost. The optimal configuration for the body armor structure with hybrid metal are steel Armox500T with thickness of 1 mm, composite thickness of 20 mm, and a quasi-isotropic configuration for composite orientation with performancecost index is 0.0179. The most significant contributing factor to the SEA value is the metal material, contributing 56.51